2017
DOI: 10.1002/ijgo.12097
|View full text |Cite
|
Sign up to set email alerts
|

Medium-term outcomes of laparoscopic sacrocolpopexy or sacrohysteropexy versus vaginal sacrospinous ligament fixation for middle compartment prolapse

Abstract: Although LSC/LSH achieved longer TVL, both groups achieved the same success rate and improvement in quality of life. Specifically, VSSLF yielded a significant improvement in bowel and urinary function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 24 publications
1
24
0
1
Order By: Relevance
“…In the case of VPP the two most accepted techniques for surgical correction are LSC and vaginal SF [ 7 ]. As mentioned before, no randomized trials have been published, investigating the superiority of one of the two approaches [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of VPP the two most accepted techniques for surgical correction are LSC and vaginal SF [ 7 ]. As mentioned before, no randomized trials have been published, investigating the superiority of one of the two approaches [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the estimated learning curve for SF required only 20 cases to complete the procedure with a favorable anatomical outcome [ 5 , 6 , 22 ]. However, even if each patient's long-term satisfaction, low morbidity rate, and acceptable cost-effectiveness should be considered the most important variables in the choice of surgery for VPP correction, data regarding these topics are still too scarce to draw any significant conclusion [ 4 , 7 ]. This is even more remarkable in the case of a second recurrence of VPP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…David-Monte ore et al observed the medium-term and long-term surgical effects in 51 patients, with an average follow-up time of 23.8 ± 8 months; 94.3% of patients had no objective recurrence [16]. Chen et al analyzed the surgical effect among 94 cases of VSSLF 1 year after the operation, where apical compartment success rate was 94.7%, and recurrence of anterior/ posterior prolapse was 16% [17]. We assume that the success rate of postoperative anatomical reduction is related to the following factors: 1.…”
Section: Sacrospinous Ligament Xation (Sslf)mentioning
confidence: 99%
“…Daher kann bei primären Defektkorrekturen des hinteren Kompartiments die routinemäßige Anwendung von synthetischen Netzen nicht empfohlen werden [12,19]. In direkten Vergleichsstudien mit der laparoskopischen Sakrokolpopexie zeigen sich ähnliche Erfolgsraten [22]. Trotz längerer Operations-und Krankenhausaufenthaltsdauer gilt die Sakrokolpopexie als Therapie der Wahl für Defekte des mittleren Kompartiments.…”
Section: B) Vaginale Netzinterpositionunclassified